A boundary value problem for cold plasma dynamics. Issue 1 (23rd January 2003) - Otway, Thomas H.
Abstract : A weak Guderley-Morawetz problem is formulated for a mixed elliptic-hyperbolic system that arises in models of wave propagation in cold plasma. Weak solutions are shown to exist in a weighted Hilbert space. This result extends the work of Yamamoto (1994).